Chondrocyte Morphology in Stiff and Soft Agarose Gels and the Influence of Fetal Calf Serum. Issue 5 (16th August 2016) - Karim, Asima; Hall, Andrew C.
Abstract : Changes to chondrocyte volume/morphology may have deleterious effects on extracellular matrix (ECM) metabolism potentially leading to cartilage deterioration and osteoarthritis (OA). The factors controlling chondrocyte properties are poorly understood, however, pericellular matrix (PCM) weakening may be involved. We have studied the density, volume, morphology, and clustering of cultured bovine articular chondrocytes within stiff (2% w/v) and soft (0.2% w/v) three‐dimensional agarose gels. Gels with encapsulated chondrocytes were cultured in Dulbecco's Modified Eagle's Medium (DMEM; fetal calf serum (FCS) 1–10%;380 mOsm) for up to 7 days. Chondrocytes were fluorescently labeled after 1, 3, and 7 days with 5‐chloromethylfluorescein‐diacetate (CMFDA) and propidium iodide (PI) or 1, 5‐bis{[2‐(di‐methylamino)ethyl]amino}‐4, 8‐dihydroxyanthracene‐9, 10‐dione (DRAQ5) to identify cytoplasmic space or DNA and imaged by confocal laser scanning microscopy (CLSM). Chondrocyte density, volume, morphology, and clustering were quantified using Volocity™ software. In stiff gels after 7 d with 10% FCS, chondrocyte density remained unaffected and morphology was relatively normal with occasional cytoplasmic processes. However, in soft gels by day 1, chondrocyte volume increased ( P  = 0.0058) and by day 7, density increased ( P  = 0.0080), along with the percentage of chondrocytes of abnormal morphology ( P  < 0.0001) and enhanced clustering ( P  < 0.05), compared to stiff gels. FCS exacerbated changes to density ( P  < 0.01), abnormal morphology ( P  < 0.001) and clustering ( P  < 0.01) compared to lower concentrations at the same gel strength. Reduced gel stiffness and/or increased FCS concentrations promoted chondrocyte proliferation and clustering, increased cell volume, and stimulated abnormal morphology, producing similar changes to those occurring in OA. The increased penetration of factors in FCS into soft gels may be important in the development of these abnormal chondrocyte properties. J. Cell. Physiol. 232: 1041–1052, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Changes to chondrocyte properties occur during the process of osteoarthritis but their role in this disorder is poorly understood. We described a three‐dimensional culture model using stiff and soft agarose and quantified chondrocyte properties of density, morphology, volume, and clustering. Some of the changes we observed are very similar to those that occur in OA and the results suggested that the penetration of serum factors in the culture medium could be responsible.